Traumatic Myocarditis in a Bitch Caused by Automobilistic Accident - Eugênio Luz, Patrick; Sayuri Medeiros Watanabe, Jaqueline; Maingué, Ana Paula; Sayuri Kono, Isabelli; Podleskis, Mariana; Lúcia Scortecci Hilst, Carmen; Mendes Pereira, Patrícia; Nelson Gava, Fábio (Acta Scientiae Veterinariae, 2025)
Background: Myocarditis is a myocardial disease with poor prognosis in dogs and cats, and the etiology can be infectious or non-infectious, as traumatic myocarditis. Traumatic myocarditis is related to ventricular and supraventricular arrhythmias due to traumas in the thx after 24 to 48 h after the episode. The diagnosis is challenging, frequently undiagnosed and tools like modified Duke Criteria can be used to obtain ante mortem diagnosis with dosage of biomarkers as troponin I (TnI), echocardiographic e electrocardiographic findings, physical exam, and hematologic alterations. Echocardiogram (ECO) can show systolic dysfunction e heteroechogenicity of the myocardium in the left ventricle, and pericardial effusion. Biomarkers such as TnI has high specificity for the cardiac tissue and can be utilized in emergency triage. The enzyme creatine kinase - MB (CK-MB) is present in the heart, kidney, intestine and lung tissue, is also used as an additional exam to investigate myocarditis. The objective is to present a rare case of traumatic myocarditis. Case: A 9-year-old mixed breed neutered bitch, weighing 10.9 kg was presented to the Veterinary Hospital of State University of Londrina (HV-UEL), Londrina, Paraná, Brazil, with the history of automobile accident 30 min ago. The patient was conscious in lateral recumbency, bilateral mydriasis and dyspnea. In their auscultation, it was noticed pulmonary crepitation and muffing heart sounds. Patient received oxygen therapy, methadone and fluid therapy. Radiography of thorax was presented by pulmonary contusion and in T-fast, had low cardiac output, discrete pleural effusion and heterogeneous and hyperechoic myocardium. Electrocardiogram (ECG) revealed sinus tachycardia, right branch block and paroxistic ventricular tachycardia, then it was administered lidocaine. Systemic arterial pressure was 50 mmHg, then continuous infusion of dobutamine was administered until it was normalized. Cardiac biomarkers troponin I and CK-MB was high. With the diagnosis of traumatic myocarditis, the patient was admitted. The day after, pulmonary contusion was improved. In the 4th day, patient was discharged. Thirteen days after, patient had normalization of the radiography and echocardiographic findings, electrocardiogram still had right branch block but with sinus rhythm. Finally, cardiac biomarkers were mildly elevated. Discussion: Immediate intervention of the case, allowed to stabilize the patient and to diagnose with pulmonary contusion by chest radiography. After the results of haematologic examination, ECG and ECO, it was possible to diagnose the patient with traumatic myocarditis using the Modified Duke’s Criteria. Studies found that ventricular arrhythmias are the most common electrocardiographic alterations in myocarditis, as we observed in this case. The use of corticosteroids is not proven to be effective, but we had positive results in our case. For the management of hypotension, dobutamine was used because of the inotropic action. The therapy for hemothorax should be focused on blood loss and fluids. Study shows that CK-MB and canine TnI was high in two patients with cardiac trauma. Both biomarkers were elevated in our case. In the follow up, the biomarkers were still elevated, leading to the suspicion that there were cicatricial lesions in the myocardium. Careful evaluation of the patient is crucial to determine every step of and emergency assistance. Myocardial lesion initiate a series of events that can lead to alterations of electrical conduction and contraction, putting the patient in life risk. Therefore, patients with history of automobile accident should be submitted to complete thoracic evaluation as thoracic radiography, electrocardiography, echocardiography, for possible myocardial alterations. And if possible, the dosage of cardiac biomarkers. Keywords: trauma, echocardiogram, electrocardiogram, cardiac biomarkers, myocardial lesion. Título: Miocardite traumática em cadela causada por acidente automobilístico Descritores: trauma, ecocardiograma, eletrocardiograma, biomarcadores cardíacos, lesão miocárdica.